Distortion Effects of Export Quota Policy: an Analysis of the China - Raw Materials Dispute - Christophe Charlier; Sarah Guillou (Fondazione Eni Enrico Mattei (FEEM), 2014)
The China - Raw Materials dispute recently arbitrated by the WTO opposed China as defendant to the US, the EU and Mexico as claimants on the somewhat unusual issue of export restrictions on natural resources. For the claimants, Chinese export restrictions on various raw materials, of which the country is a major producer, create shortages in foreign markets increasing the prices of these goods. China defends export limitations by presenting them as a natural resource conserving policy. This paper offers a theoretical analysis of the dispute with the help of a model of a monopoly extracting a non-renewable resource and selling it on both the domestic and foreign markets. The theoretical results focus on the effects of imposing an export quota on quantities, prices and price distortion. Given the crucial importance of demand elasticity in this theoretical understanding of the conflict, the empirical part of the paper provides estimates of import demand elasticity of the parties for each product concerned in the case. The model and the empirical results challenge the ideas that an export quota always favours conservation of natural resource, that a higher foreign price necessarily follows this policy and that it inherently increases price distortion and therefore discrimination.
Keywords: F13; F18; F51; K33; Q37; 330; Export Restrictions; WTO; Exhaustible Natural Resources; Price Discrimination; Article XX of the GATT 1994